Effects of tumor necrosis factor-β (TNF-β) 252A>G polymorphism on the development of migraine: a meta-analysis. - Ruozhuo Liu (Public Library of Science (PLoS), 2014)
Background and objective Genetic factors including TNF-β have been considered as important components in the aetiology of migraine. Many studies have investigated the association between TNF-β 252A>G polymorphism and migraine risk, with debatable results. This study was designed to examine whether the TNF-β 252A>G polymorphism confers genetic susceptibility to migraine in diverse populations. Method Studies eligible for this meta-analysis were searched in the PubMed, Embase, and CNKI by using the keywords "tumor necrosis factor", "TNF", "252A>G", "rs909253", "polymorphism", "polymorphisms", "variant", "SNP", combined with "migraine" or "migraine with aura (MA)" or "migraine without aura (MO)". Pooled ORs and 95% CI were appropriately calculated using the fixed-effect model. Results We finally included a total of seven studies, providing 5 557 migraineurs and 20 543 unrelated healthy controls. Meta-analysis results showed no statistical evidence of a significant association between TNF-β 252A>G polymorphism and overall migraine risk. Stratified analyses by type of migraine and gender revealed similar results. Interestingly, an OR with 95% CI representing an increased migraine risk was indicated in Asians under the recessive model (GG vs. AG + AA: OR, 1.38; 95%CI, 1.04-1.84; P for heterogeneity, 0.665). Conclusions Our findings appear to support the hypothesis that genetic variability of 252A>G polymorphism in TNF region may modulate risk of migraine in the population of Asian ancestry.